A metal–metalloporphyrin framework based on an octatopic porphyrin ligand for chemical fixation of CO2 with aziridines. Issue 10 (21st December 2017) - Wang, Xun; Gao, Wen-Yang; Niu, Zheng; Wojtas, Lukasz; Perman, Jason A.; Chen, Yu-Sheng; Li, Zhong; Aguila, Briana; Ma, Shengqian
Abstract : A new porous metal–metalloporphyrin framework, MMPF-10, was synthesized for CO2 cycloaddition with aziridines. Abstract : A new porous metal–metalloporphyrin framework, MMPF-10, has been constructed from an octatopic porphyrin ligand, which links copper paddlewheel units to form a framework withfmj topology. In situ metallation of the porphyrin ligands provides MMPF-10 with two unique accessible Cu(ii ) centers. This allows it to behave as an efficient Lewis acid catalyst in the first reported reaction of CO2 with aziridines to synthesize oxazolidinones catalyzed by an MMPF.